Zaczynajac od moich ulic - Milosz, Czeslaw (Wroclaw : Wydawn. Dolnoslaskie, 1990)
Collection of essays and articles by this Nobel Prize winning author.
1. Wilno -- 2. Stare awangrady -- 3. Portrety -- 4. Pozegnania -- 5. Przemowienia.
"Przedruk za: Instytut Literacki, Paryz 1985" -- page facing t.p.